TEPUNG UBI JALAR SEBAGAI SUMBER ENERGI PAKAN DALAM UPAYA PENINGKATAN KUALITAS KARKAS AYAM PEDAGING - Nonok Supartini; Sumarno Sumarno (BUANA SAINS, 2010)
This research is executed in Laboratory Field Ranch of University of Tribhuwana Tunggadewi Malang. The aims of this research is to determine influence of sweet potato creep as source of energy to crabbed weight, chest weight, heavy of thigh, and abdominal fat weight. Research items the used is broiler counted 80 tail have male sex to of finisher weighing of Wal 963,37 + 31,23 g, which is used in this research is Strain Lohman Platinum which produced by PT. Multi Breeder Adirama Indonesia. Method which is used in research is attempt method by using complete random device which consist of 4 treatment where every treatment repeated by 5 times and each restating consist of 4 chicken tail. This research can be concluded that gift of sweet potato creep as source of energy give result of crabbed weight P0 1199,40; P1 1138,98; P2 1076,60; P3 1038,20 chest weight of P0 358,08; P1 366,60; P2 337,80; P3 323,40 thigh weight of P0 479,80; P1 472,94; P2 468,40; P3 442,00 and abdominal fat weight of P0 33,20; P1 35,60; P2 25,40; P3 27,80. Chest weight, heavy weight, thigh weight and weight of abdominal fat which is equal to maize but gift 10% flour of sweet potato creep from totalizeing ransom tend to give result of better. Is suggested to increase heavily chest, heavy of laboured by abdominal fat and thigh of percentage of treatment food of sweet potato maximal 10%